A Perspective‐Taking Theory of Open‐Mindedness: Confronting the Challenge of Motivated Reasoning. Issue 5 (13th December 2021) - Southworth, James
ABSTRACT: Previous research on open‐mindedness, whether by critical thinking researchers, philosophers of education, or intellectual virtue theorists, has not sufficiently addressed the challenge posed by cognitive bias, particularly motivated reasoning. How can students develop their open‐mindedness when they are often motivated to preserve their prior beliefs? In this paper, James Southworth proposes a theory of open‐mindedness that attempts to confront the problem of motivated reasoning. He argues that to be open‐minded is to be receptive to ideas that challenge one's prior beliefs. He discusses two central and interrelated aspects of receptivity: (1) a motivation toward the truth, and (2) an ability and disposition to take on the perspective of an individual(s) who holds an opposing belief. While open‐mindedness includes cognitive, affective, and motivational dimensions, Southworth argues that it is narrow in scope. Open‐mindedness does not concern neutral scenarios. Moreover, open‐mindedness does not require the ability to reason well. Southworth concludes by considering some practical implications of this account with respect to reading and writing practices in higher education.